Prevalence of Chronic Ankle Instability and Associated Symptoms in University Dance Majors: An Exploratory Study. Issue 4 (December 2014) - Simon, Janet; Hall, Emily; Docherty, Carrie
Previous investigations have established that dancers suffer a large number of injuries to the lower leg, foot, and ankle, with a portion of these being significant time loss injuries or in some cases career ending. Lateral ankle sprain is a common injury in dancers and can often lead to recurrent instability and repetitive injuries. Research in other active populations has linked ankle sprains to the development of chronic ankle instability (CAI). Therefore, the purpose of this study was to identify the prevalence of CAI and related symptoms of ankle sprain in a student dance population. Individuals were included if they were currently a modern or ballet dance major at the investigators' university (exclusion criterion: a history of fracture or surgery in the lower extremities). A self-reported demographic questionnaire and the Identification of Functional Ankle Instability survey were used to identify the presence and characteristics of CAI. A total of 83 questionnaires were collected, and after exclusions, 77 participants remained: 43 modern dancers and 34 ballet dancers (10 males and 67 females, mean age 19.61 ± 2.53 years, mean dance experience 13.61 ± 3.16 years). Of all dancers surveyed, 41 (53.2%) had CAI, and of those 24 (58.5%) were modern dancers, and 17 (41.5%) were ballet dancers. When looking only at those dancers who had a previous lateral ankle sprain, 75.9% were identified as having CAI. Chronic Ankle Instability can create long-term problems for anyone but especially female dancers, who place extreme stress on their feet and ankles from being en pointe or demi-pointe. It is important to educate dancers, instructors, and medical staff of the importance of recognizing CAI and seeking medical care for ankle sprains and their residual symptoms.